2013
DOI: 10.1128/aem.01443-13
|View full text |Cite
|
Sign up to set email alerts
|

Shared Mycobacterium avium Genotypes Observed among Unlinked Clinical and Environmental Isolates

Abstract: e Our understanding of the sources of Mycobacterium avium infection is partially based on genotypic matching of pathogen isolates from cases and environmental sources. These approaches assume that genotypic identity is rare in isolates from unlinked cases or sources. To test this assumption, a high-resolution PCR-based genotyping approach, large-sequence polymorphism (LSP)-mycobacterial interspersed repetitive unit-variable-number tandem repeat (MIRU-VNTR), was selected and used to analyze clinical and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
2
1
Order By: Relevance
“…The discriminatory power experienced in the present study is slightly reduced compared to what has been described by others [27, 32, 34]. This could be explained by the epidemiologic link between the isolates, as multiple isolates were retrieved from the same farms and production sites and also from the same pigs.…”
Section: Discussioncontrasting
confidence: 84%
“…The discriminatory power experienced in the present study is slightly reduced compared to what has been described by others [27, 32, 34]. This could be explained by the epidemiologic link between the isolates, as multiple isolates were retrieved from the same farms and production sites and also from the same pigs.…”
Section: Discussioncontrasting
confidence: 84%
“…Overall, the results obtained through the VNTR analysis showed that most MAH strains, isolated in recent years, displayed a close genetic relationship, indicating that the MAH genotypes are quite homogeneous in our geographical area, confirming our previous results for the years prior to 2010. This finding is consistent with those of other studies demonstrating that strains of MAH exhibit geographical differences in genetic diversity (Dirac et al, 2013;Ichikawa et al, 2015;Iwamoto et al, 2012;Kalvisa et al, 2016). Such genotypic stability of the MAH strain population circulating in our region supports the hypothesis of the presence of possible local sources of infection and transmission pathways at the local level, as suggested in recent studies demonstrating different degrees of genetic correlation between human, swine and environmental MAH strains depending on the geographical area (Iwamoto et al, 2012;Lahiri et al, 2014;Muwonge et al, 2014;Nishiuchi et al, 2017).…”
Section: Genotyping and Clustering Analysis Of Mah Isolatessupporting
confidence: 93%
“…For a few strains, the subspecies identification was also confirmed by sequencing of the hsp65 gene using the classification proposed by Turenne et al [24] and the method described by Dirac et al [25].…”
Section: Gene Sequencingmentioning
confidence: 99%